2012
DOI: 10.2135/cropsci2011.10.0579
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and Plant Water Use Efficiency in Cocksfoot and Tall Fescue Accessions under Differing Soil Water Availability

Abstract: Water availability is one of the most important limiting factors in plant production worldwide. Such limitation is expected to increase in regions with a Mediterranean climate type during the next few decades. The objectives of this study were to evaluate plant water use efficiency (WUE) in contrasting accessions of two perennial grasses, Dactylis glomerata L. (cocksfoot) and Festuca arundinacea Schreb. [syn. Lolium arundinaceum (Schreb.) Darbysh.] (tall fescue), under two different water availability regimes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…Stomatal conductance explains more variation in the WUE L than does P n (Easlon et al, 2014). The results from this study showed that the WUE L parameters did not show a consistent relationship with the WUE g or Δ 13 C values, in agreement with previous studies (Gulías et al, 2012; Tomás et al, 2012). Δ 13 C was significantly correlated with the average soil moisture conditions, while the WUE L was connected with the soil water content at the time the measurements were taken; therefore, WUE L was correlated with the Δ 13 C only when the WUE L was measured at the time when the soil moisture conditions were similar to the average soil moisture conditions during the growth period.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Stomatal conductance explains more variation in the WUE L than does P n (Easlon et al, 2014). The results from this study showed that the WUE L parameters did not show a consistent relationship with the WUE g or Δ 13 C values, in agreement with previous studies (Gulías et al, 2012; Tomás et al, 2012). Δ 13 C was significantly correlated with the average soil moisture conditions, while the WUE L was connected with the soil water content at the time the measurements were taken; therefore, WUE L was correlated with the Δ 13 C only when the WUE L was measured at the time when the soil moisture conditions were similar to the average soil moisture conditions during the growth period.…”
Section: Discussionsupporting
confidence: 87%
“…Improving the agronomic WUE can be considered the ultimate target (Condon et al, 2004). The WUE at the grain‐yield level is usually difficult to accurately determine (Gulías et al, 2012). Instantaneous gas exchange on a photosynthetic basis can be measured rapidly and easy, and is thus widely used as an alternative approach for measuring the WUE (Condon et al, 2004; Farquhar and Richards, 1984; Farquhar et al, 1989; Qiu et al, 2008; Rizza et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf gas exchange measurements are limited to a particular leaf and specific time, and may not accurately represent long-term or whole-plant processes. When calculated using leaf gas exchange measurements, WUE is not always consistent with the final WUE based on biomass and yield (Gulías et al 2012;Tomás et al 2012;Wang et al 2013). In this study, it was demonstrated that, although WUE i was unaffected, the overall water use efficiency (WUE a ) of an irrigation system can be improved by adopting sensor-control.…”
Section: Plant Growth Photosynthetic Activity and Tissue Analysismentioning
confidence: 83%
“…As expected in water replete growth conditions, we found lower d 13 C bulk associated with high moisture and fast growth rate to benefit grain production based on the negative relationships between d 13 C bulk and grain yield. Negative relationships have also been found in response to water limitation (as determined by d 13 C; Gulías et al, 2012;Tomás et al, 2012;Wang et al, 2016), and it is this opportunity that we seek to find high-yielding WUE cultivars that deviate from the overall inverse relation. Although this approach has merit, one complication is that the interaction of multiple environmental factors and physiological and biochemical differences may complicate the use of d 13 C as a measure of WUE, particularly between cultivars (Condon et al, 2004).…”
Section: Testing For Grain Yield Associated With Leaf Level Estimatesmentioning
confidence: 99%